Eer en schaamte in het Nieuwe Testament Implicaties voor het spreken over heil - Klinker-De Klerck, M. (2023)
The vast majority of societies worldwide are primarily shame cultures. Honour and shame, important values in the social dynamics of these societies, have also profoundly influenced New Testament writings. This has implications for the concept of salvation. First, I briefly introduce "shame culture" as the bedrock of the New Testament. Second, I illuminate the gospel as a message of salvation from a shame perspective, illustrating this with data from the New Testament. Not only guilt, but rather sacred shame is animportant component of the human problem. Salvation in Christ is then interpreted not primarily as the satisfaction of a debt that arose after original sin, but as the removal of irreparable shame resulting from that same original sin.
Der Rubrikentitel ist auf dem gedruckten Heft nicht zu sehen. Der Rubrikentitel ist von der Internetseite der Zeitschrift entnommen